PENERAPAN PROGRAM LITERASI SEBAGAI PENINGKATAN KEMAMPUAN BACA TULIS SISWA DI SD NEGERI TEMAS 01 KOTA BATU - Novinda Aswana Putri; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The research conducted on the application of literacy programs as an increase in students' reading skills in SD Negeri 01 Kota Batu. The research method used is qualitative research using data collection techniques consisting of observation, interviews, and documentation. In this study, the study found the ability in SD Negeri Temas 01 Batu, the implementation of the literacy program at Temas 01 SD Negeri Batu, and the supporting and inhibiting factors of the literacy program. The results of this study are the students' reading skills that have been enhanced by the literacy program. The literacy program implemented is the habit of reading 15 minutes before the lesson, Tuesday and Thursday literacy activities, and library utilization. Literacy implementation program starts from training, development, and implementation in learning. As a factor supporting literacy programs such as socialization, creating literate spaces, creating reading corners, providing facilities and infrastructure. While the inhibiting factors that contain a minimum source of reading and lack of interest in reading students.Keywords: Literacy Program, Literacy Ability